Analisis Resiko Ergonomi pada Aktivitas Kerja dengan Menggunakan Metode Nordic Body Maps di Departemen Housekeeping pada Favehotel Braga - Fina Cindi Sabila; Ayi Tejaningrum (Fakultas Ekonomi & Bisnis, Univ, 2026)
This reasearch aims to analyze the process of ergonomic risk in the activities of the housekeeping department at Favehotel Braga using the Nordic body maps (NMB) method to improve the productivity of housekeeping workers. The research method used quantitative with description of NBM questionnaires to 12 repondents or housekeeping wokers. The results of the research show that the recapitulation pf the questionneaire using the NBM method indicates that the body parts experiencing complanits are waist at 4,68%, the left shoulder at 4,15 %, the right shoulder at 4,02%, and the back at 4,15%. Resulting in the total questionnaire recapitulation score of 747 with an average of 62,25, which falls into the moderate risk category meaning that corrective action is required. These complaints are cause by repetitive movements during room cleaning and other hotel area cleaning activities. Based on the comparison with ergonomic principles discrepancies were found between actual working postures and ergonomic prinsiples, so it is recommended to improve work techiques such as cleaning hotel room and pushing trolley in accordance with ergonomic prinsiples which can reduce the risk of injury and improve work productivity. This research is expeted to serve as a reference for housekeeping workers in applying ergonomic prinsiples to enhance worker productivity.